1985
DOI: 10.1001/jama.1985.03360050065027
|View full text |Cite
|
Sign up to set email alerts
|

Perivenular Fibrosis as Precursor Lesion of Cirrhosis

Abstract: Thirty-four male alcoholics underwent sequential liver biopsies as part of their evaluation. Of 19 subjects with simple fatty livers, only three showed progression of liver disease: one developed perivenular fibrosis after two years; a second showed no progression after three years, but developed perivenular fibrosis after four years; the third subject likewise showed no progression after one year, but developed incomplete cirrhosis after six years. In contrast, of 15 subjects with perivenular fibrosis at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(58 citation statements)
references
References 18 publications
1
56
0
1
Order By: Relevance
“…Fibrous extension is also a histological feature associated with thickened central veins in the liver of patients with alcoholic hepatitis (Chevallier et al, 1994). We found that 49.2% of elderly cadaveric livers had CVF, comparable with the 44% incidence found in young adult heavy alcohol drinkers, aged 47.6 AE 3.1 years (Worner and Lieber, 1985). Sequential biopsies conducted by these investigators revealed that alcoholics with CVF in early stages of fatty liver are more susceptible to progression to more severe stages of fibrosis and ultimately cirrhosis.…”
Section: Discussionsupporting
confidence: 78%
“…Fibrous extension is also a histological feature associated with thickened central veins in the liver of patients with alcoholic hepatitis (Chevallier et al, 1994). We found that 49.2% of elderly cadaveric livers had CVF, comparable with the 44% incidence found in young adult heavy alcohol drinkers, aged 47.6 AE 3.1 years (Worner and Lieber, 1985). Sequential biopsies conducted by these investigators revealed that alcoholics with CVF in early stages of fatty liver are more susceptible to progression to more severe stages of fibrosis and ultimately cirrhosis.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, we have shown for the first time that recurrence of alcoholic hepatitis is a common event in patients with alcoholic hepatitis on the It has been reported that patients with perivenular fibrosis show rapid fibrosis progression. 14,15,18 However, the importance of perivenular fibrosis in the pathogenesis of alcohol-induced liver injury remains unknown, as studies evaluating this lesion were performed on a small cohort and multivariate analysis was not performed. In the present study, perivenular fibrosis did not predict fibrosis progression, as the trend towards significance in univariate analysis disappeared in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…12 In alcoholic liver disease, studies using a design of repeated biopsies have provided valuable information, [13][14][15][16][17][18] and suggest steatosis as a risk factor for development of cirrhosis. 17 However, in those studies, the number of patients with repeated liver biopsies, ranging from 16 out of 76 19 to 39 out of 88 17 was not sufficient to determine the evolution of patients according to their initial histological diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Acetaldehyde, a potential prothe development of liver fibrosis. We have studied the oxidant factor linked to ethanol metabolism, has been proeffect of neutrophil-derived reactive oxygen species posed as a mediator of fibrogenesis in alcoholic liver disease.…”
mentioning
confidence: 99%